Outcomes of Renal Stone Surgery Performed Either as Predonation or Ex Vivo Bench Procedure in Renal Grafts from Living Donors: A Systematic Review. (1st December 2020) - Longo, Nicola; Calogero, Armando; Creta, Massimiliano; Celentano, Giuseppe; Napolitano, Luigi; Capece, Marco; La Rocca, Roberto; Sagnelli, Caterina; Carlomagno, Nicola; Peluso, Gaia; Pagano, Teresa; Campanile, Silvia; et al.
Abstract : Aims . We aimed to summarize available evidence about intraoperative and postoperative donors' and recipients' outcomes following stone surgery in renal grafts from living donors performed either before donation or as ex vivo bench surgery at the time of living-donor nephrectomy. Methods . A systematic review of PubMed, ISI Web of Knowledge, and Scopus databases was performed in September 2020. We included full papers that met the following criteria: original research, English language, human studies, and describing the results of stone surgery in renal grafts from living donors performed either before transplantation or as ex vivo bench surgery. Results . We identified 11 studies involving 106 patients aged between 22 and 72 years. Predonation and bench stone surgery was performed in 9 (8.5%) and 96 (90.6%) patients, respectively. Predonation stone surgery involved extracorporeal shock wave lithotripsy, retrograde intrarenal surgery, and percutaneous nephrolithotomy in 8, 1, and 1 patient, respectively. The overall success rate of predonation stone surgery was 78%, and the complication rate was 0%. Bench stone surgery involved ureteroscopy, pyelolithotomy, or a combination of both in 79 (82.3%), 10 (10.4%), and 7 (7.3%) cases, respectively, with an overall success rate of 95.8% and an overall complication rate of 9.37%. Conclusions . Predonation and bench stone surgery in grafts from living donors represents efficacious and safe procedures. Further studies on wider series with a longer follow-up are required.